2022
DOI: 10.1101/2022.04.04.487016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural systems underlying RDoC social constructs: An activation likelihood estimation meta-analysis

Abstract: ObjectiveNeuroscientists have sought to identify the underlying neural systems supporting mental processes involved in social cognition. These processes allow us to interact and communicate with others, form social relationships, and navigate the social world. Through the use of NIMH’s Research Domain Criteria (RDoC) framework, we evaluated consensus among hundreds of studies that examined brain activity during social and social cognition tasks to elucidate, at a large scale, regions comprising the “social bra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…This variable-centered analysis revealed that among the full sample, bilateral TPJ were significantly negatively associated with US orientation, such that as US orientation increased, fALFF values in the TPJ decreased (Table S1). These results likely reflect this region's role in social affiliations (42) and speculate that TPJ hyperactivity may be linked to challenges in identity development as youth navigate US life within a family system that is not fully engaged with the broader US culture. Importantly, our investigation of ABCD caregiver acculturation profiles at baseline identified a subset of Hispanic/Latinx youth that are at higher risk for adverse outcomes at the beginning of adolescence, a critical socioemotional neurodevelopmental period wherein psychopathology often emerges (70,71).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…This variable-centered analysis revealed that among the full sample, bilateral TPJ were significantly negatively associated with US orientation, such that as US orientation increased, fALFF values in the TPJ decreased (Table S1). These results likely reflect this region's role in social affiliations (42) and speculate that TPJ hyperactivity may be linked to challenges in identity development as youth navigate US life within a family system that is not fully engaged with the broader US culture. Importantly, our investigation of ABCD caregiver acculturation profiles at baseline identified a subset of Hispanic/Latinx youth that are at higher risk for adverse outcomes at the beginning of adolescence, a critical socioemotional neurodevelopmental period wherein psychopathology often emerges (70,71).…”
Section: Discussionmentioning
confidence: 94%
“…Resting state functional magnetic resonance imaging (rs-fMRI) analyses were preregistered (https://osf.io/mkdw3/). We focused on five meta-analytically-defined regions of interest (ROIs) associated with self-and affiliation-related processing (42), including the (1) vmPFC, (2) left insula, (3) right insula, (4) left TPJ, and (5) right TPJ (Fig. S1).…”
Section: Resting State Fmri Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Broadly defined, SP comprises processes and knowledge that mediate the perception and understanding of the self and others, as well as the responses that are generated within a social context (reception and production of facial and non-facial communication) (Koudys et al, 2019). A recent meta-analysis used the activation likelihood estimate method and reported that the medial prefrontal cortex (mPFC), anterior cingulate cortex (ACC), posterior cingulate cortex (PCC), temporoparietal junction (TPJ), bilateral insula, amygdala, fusiform gyrus, precuneus, and thalamus are the neural underpinnings of the SP domain (Lobo et al, 2022).…”
Section: Social Processes (Sp)mentioning
confidence: 99%